QUALITY ANALYSIS OF EDUCATIONAL SERVICES ON STUDENT RESPONSE THROUGH QFD APPROACH TO IMPROVE PERFORMANCE OF UNIVERSITY OF 17 AGUSTUS 1945 (UNTAG) BANYUWANGI - Endang Suprihatin (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2018)
ABSTRACT University of 17 Agustus 1945 or UNTAG Banyuwangi is a private university, where the source of mostly income comes from students or in other words that all forms of activities carried out are geared towards students, therefore efforts to acquire new students from year to year must be increased, one the effort that must be done is that UNTAG Banyuwangi is in addition to implementing the PMB program (admission of new students) with effective and great promotions as well as keeping students who have attended UNTAG Banyuwangi not stop studying midway. Therefore it is necessary to conduct research on the analysis of the quality of education services to the students' responses through Quality Function Deployment (QFD) approach in improving the performance of UNTAG Banyuwangi. The sampling result of the level of importance and satisfaction on the dimensions of infrastructure, learning process, human resources, curriculum and student affairs of all variables have corrected total correlation value greater than 0.1430 (r table value) for each dimension, of the sample questionnaire of 83 students have been valid. For the value of  (alpha) obtained each dimension is also greater than 0.05, so it can be concluded that the data is reliable. The results of the analysis of the strengths and weaknesses of UNTAG are based on their importance and level of satisfaction are then plotted into quadrant maps Variables included in quadrant IV are weaknesses for UNTAG Banyuwangi educational institutions, namely: How to teach Lecturers, Strategies for teaching lecturers are understood by students, The ability of lecturers to use learning tools white board, UHP, LCD, lecturers in teaching in class, how to deliver material, how to answer student questions, quality of lecturers in conducting research, community service, infrastructure (office, classroom, laboratory room, studio , library rooms, experimental gardens, etc. except lecturer room), facilities / equipment used in the learning process such as computers, software and hardware. HOQ analysis in the technical response matrix derived from the way the UNTAG Banyuwangi Institute in answering the request of the Student (Hows). After conducting an interview with the leadership, namely the Rector, the selected technical response was: 1. Providing assistance to the Lecturer to develop the substance of the field of knowledge 2. Sending Lecturers to take part in the learning method training 3. Implementing a cycle of good practice learning processes. 4. Inventory of land, buildings and all the room. 5. Trying to obtain laboratory equipment and information technology. Keywords: quality of service, Quality Function Deployment (QFD), Higher Education